2001
DOI: 10.1089/10799900152434358
|View full text |Cite
|
Sign up to set email alerts
|

IFN-γInhibits Lipopolysaccharide-Induced Interleukin-1βin Primary Murine Macrophages via a Stat1-Dependent Pathway

Abstract: Interleukin-1 (IL-1) plays an important role in host defenses against microbial pathogens. Excessive production of this cytokine, however, may be responsible in part for the lethality observed during sepsis. Our studies show that interferon-gamma (IFN-gamma) downregulates lipopolysaccharide (LPS)-induced interleukin-1beta (IL-1beta) transcription in primary macrophages. This phenomenon does not occur in splenocytes or bone marrow-derived macrophages from signal transducer and activator of transcription (Stat1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 40 publications
2
17
0
Order By: Relevance
“…3D), confirming the results of previous studies (22,24). Of note, under these conditions, downregulation of IL-1b was accompanied by increased NO concentrations and vice versa (compare Fig.…”
Section: Ifn-g Inhibits Il-1b Transcription Without Affecting Mrna Stsupporting
confidence: 91%
See 3 more Smart Citations
“…3D), confirming the results of previous studies (22,24). Of note, under these conditions, downregulation of IL-1b was accompanied by increased NO concentrations and vice versa (compare Fig.…”
Section: Ifn-g Inhibits Il-1b Transcription Without Affecting Mrna Stsupporting
confidence: 91%
“…It was reported that IFN-g can downregulate IL-1b production in response to LPS stimulation and infection with Mycobacterium tuberculosis, as well as in models of autoimmune diseases, like collagen-induced arthritis, both in vitro and in vivo (21-24, 36, 37). Several reports indicated that IFN-g-mediated suppression of LPS-induced IL-1b occurred at the level of transcription (21)(22)(23). Although most studies did not further analyze the underlying mechanism, De Boer et al (22) demonstrated that this transcriptional silencing was crucially dependent on IFN-g-induced NO, because pharmacological inhibition of iNOS reversed the IFN-gmediated phenotype.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Serum IFN-␥ and IL-1␤ concentrations were determined by ELISA using R4-6A2/XMG1.1 (BD PharMingen, San Diego, CA; IFN-␥) and PM425B/MM 425B (Endogen, Woburn, MA; IL-1␤) Ab pairs, as described (37). IL-18 was measured using a mouse IL-18 detection ELISA kit (Medical and Biological Laboratories, Naka-ku Nagoya, Japan), according to the manufacturer's instructions, while ELISA for IL-12 (p70) was performed using Duoset system (R&D Systems), according to the manufacturer's instructions.…”
Section: Cytokine Measurementsmentioning
confidence: 99%